6-Formylindolo[3,2-b]carbazole, a Potent Ligand for the Aryl Hydrocarbon Receptor Produced Both Endogenously and by Microorganisms, can Either Promote or Restrain Inflammatory Responses - Rannug, Agneta (Frontiers in Toxicology, 2022)
The aryl hydrocarbon receptor (AHR) binds major physiological modifiers of the immune system. The endogenous 6-formylindolo[3,2-b]carbazole (FICZ), which binds with highest affinity, plays a well-documented role in maintaining the homeostasis of the intestines and skin. The effects of transient activation of AHR by FICZ differ from those associated with continuous stimulation and, depending on the dose, include either differentiation into T helper 17 cells that express proinflammatory cytokines or into regulatory T cells or macrophages with anti-inflammatory properties. Moreover, in experimental models of human diseases high doses stimulate the production of immunosuppressive cytokines and suppress pathogenic autoimmunity. In our earlier studies we characterized the formation of FICZ from tryptophan via the precursor molecules indole-3-pyruvate and indole-3-acetaldehyde. In the gut formation of these precursor molecules is catalyzed by microbial aromatic-amino-acid transaminase ArAT. Interestingly, tryptophan can also be converted into indole-3-pyruvate by L-amino acid oxidase Il4I1, which is secreted by host immune cells. By thus generating derivatives of tryptophan that activate AHR, Il4I1 may have a role to play in anti-inflammatory responses, as well as in a tumor escape mechanism that reduces survival in cancer patients. The realization that FICZ can be produced from tryptophan by sunlight, by enzymes expressed in our cells (Il4I1), and by microorganisms as well makes it highly likely that this compound is ubiquitous in humans. A diurnal oscillation in the level of FICZ that depends on the production by the fluctuating number of microbes might influence not only intestinal and dermal immunity locally, but also systemic immunity.